The Role of Digital Marketing and Service Quality in Shaping Patient Decisions to Choose Clinics in Bandung City - Liyenka Belusi Tantra; Kartika Imasari Tjiptodjojo (Jurnal Informatika Ekonomi Bisnis, 2026)
The growth of the healthcare industry, especially in Bandung, has created a competitive environment, requiring clinics to adopt digital marketing strategies and maintain service quality to attract patients' decisions in seeking treatment. Technological developments in the healthcare world have driven changes in patient behaviour in seeking healthcare information and services. This study aims to analyse the influence of digital marketing and service quality on the decision to choose a clinic in Bandung. Using a quantitative causal explanatory approach, data were collected through an online questionnaire from 150 respondents selected using a purposive sampling technique. Respondent criteria included domicile in Bandung, active social media users, and having visited a clinic in the last 6 months. The data were analysed using PLS-SEM with the Smart PLS tool. The results showed that both digital marketing and service quality had a positive and significant influence on the decision to choose a clinic. Digital marketing strategies were found to have a slightly greater influence compared to service quality, contributing 38% to people's decisions in choosing a clinic in Bandung. The practical implications of this study suggest that clinic managers should be more active in managing digital platforms while maintaining and promoting higher-quality services to gain more loyal patients.